Occupationally Acquired American Cutaneous Leishmaniasis - Maria Edileuza Felinto de Brito; Maria Sandra Andrade; Éricka Lima de Almeida; Ângela Cristina Rapela Medeiros; Roberto Pereira Werkhäuser; Ana Isabele Freitas de Araújo; Sinval Pinto Brandão-Filho; Alzira Maria Paiva de Almeida; Eduardo Henrique Gomes Rodrigues (Case Reports in Dermatological Medicine)
We report two occupationally acquired cases of American cutaneous leishmaniasis (ACL): one accidental laboratory autoinoculation by contaminated needlestick while handling an ACL lesion sample, and one acquired during field studies on bird biology. Polymerase chain reaction (PCR) assays of patient lesions were positive for Leishmania, subgenus Viannia. One isolate was obtained by culture (from patient 2 biopsy samples) and characterized as Leishmania (Viannia) naiffi through an indirect immunofluorescence assay (IFA) with species-specific monoclonal antibodies (mAbs) and by multilocus enzyme electrophoresis (MLEE). Patients were successfully treated with N-methyl-glucamine. These two cases highlight the potential risks of laboratory and field work and the need to comply with strict biosafety procedures in daily routines. The swab collection method, coupled with PCR detection, has greatly improved ACL laboratory diagnosis.